Human Errors in Structural Design and Construction in the United Arab Emirates - Al Amouri, Ali Yousef Ali (2012)
A Master of Science thesis in Civil Engineering by Ali Yousef Ali Al Amouri entitled, "Human Errors in Structural Design and Construction in the United Arab Emirates," submitted in June 2012. Thesis advisor is Dr. Sami Tabsh. Available are both soft and hard copies of the thesis.